RESULTADOS DE LA EXTIRPACION DEL LOBULO ANTERIOR DEL CEREBELO EN EL PERRO - MANDOKI ORTIZ, J; ALCALDE OBRADOR, S (Instituto de Salubridad Publica, CD MEXICO, DF, MEX, 1943)
Periodic electrical stimulation with an alternating current (1-4 volts) of the motor cortex of the brain of the cat produced a fairly uniform motor response Intense faradic stimulation (10-20 secs) simultaneously applied to adjacent parts of the cortex
BOL INST ESTUD MED BIOL
Keywords: RESULTADOS, EXTIRPACION, LOBULO ANTERIOR, CEREBELO, PERRO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL